Interaction of Plasma Kallikrein with Protein C Inhibitor in Purified Mixtures and in Plasma - España, Francisco; Estelles, Amparo; Griffin, John H; Aznar, Justo (Thrombosis and Haemostasis, 1991)
The interaction between plasma kallikrein (KK) and protein C inhibitor (PCI) and the influence of KK on the complex formation between activated protein C (APC) and PCI was studied in purified systems as well as in plasma in order to assess the significance of these reactions in the plasma milieu. PCI complexed to KK (KK: PCI) or to APC (APC: PCI) was measured by sandwich ELISA’s using antibodies directed against each protein in the complexes. The formation of KK: PCI complexes assayed by this method paralleled the inhibition of KK amidolytic activity by PCI in purified system. Incubation of normal plasma (NHP) at 4 °C, which can induce prekallikrein activation due to cold activation, resulted in PCI inactivation and appearance of KK: PCI complexes. PCI activity fell to 35% of the NHp and 1.2 μ/ml of KK: PCI complex was formed. However, incubation of NHP at room temperature or of prekallikrein deficient plasma at 4 °C did not result in significant decrease of PCI activity. Thus the PCI inactivation was associated with prekallikrein activation and complexation to PCI following cold activation. Incubation of exogenous purified KK with NHP resulted in PCI inactivation and complexation with KK in a temperaturedependent manner. Addition of 2.8 μ/ml KK to plasma at 4 °C resulted in the inactivation of 55% of plasma PCI and the formation of 0.9 μ/ml KK: PCI which represents 21% of the KK added, whereas at 37 °C PCI was inactivated to 30% and only 0.30 μg/ml KK: PCI complexes were measured. These results indicate that PCI is a major KK inhibitor at 4 °C. At 37 °C, PCI accounted for aborfi 7% of the inhibition of the KK added. In separate experiments, following addition of 2.5 μg/ml APC to NHR more than 1 μg/ml of APC: PCI complex was formed in 3 h. When NHP was prior incubated with KK, PCI activity decreased to 10% of that of the normal plasma. Subsequent addition of APC to the plasma treated with KK resulted in formation of only 35 μg/ml of APC: PCI complex compared to 1,350 μg/ml when plasma was not previously incubated with KK. These results indicate that PCI could play a physiological role in the inhibition of plasma KK, and that, in turn, plasma KK can either complex to or inactivate plasma PCI. Thus, KK could modulate the PCI inhibition of APC in plasma.